2023
DOI: 10.1007/s40710-023-00667-2
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Carbon Capture and Biocementation through the Carbonic Anhydrase (CA) Activity of Microorganisms -a Review and Outlook

Wilson Mwandira,
Maria Mavroulidou,
Michael J. Gunn
et al.

Abstract: Biocementation, i.e., the production of biomimetic cement through the metabolic activity of microorganisms, offers exciting new prospects for various civil and environmental engineering applications. This paper presents a systematic literature review on a biocementation pathway, which uses the carbonic anhydrase (CA) activity of microorganisms that sequester CO2 to produce biocement. The aim is the future development of this technique for civil and (geo-)environmental engineering applications towards CO2-neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 205 publications
0
1
0
Order By: Relevance
“…In contrast, we found that the importance rank of the pH value is the first component for Ecological Site and Ecosite (U8/Y9). The pH plays a crucial role in cementation, affecting microbial growth, metabolism/enzymatic activity, calcite solubility and crystallization, and biomineral formation (Mwandira et al 2023). This indicated that soil condition plays a significant role at the lower level.…”
Section: Assessments Of the Component Effect And Importance Factors A...mentioning
confidence: 99%
“…In contrast, we found that the importance rank of the pH value is the first component for Ecological Site and Ecosite (U8/Y9). The pH plays a crucial role in cementation, affecting microbial growth, metabolism/enzymatic activity, calcite solubility and crystallization, and biomineral formation (Mwandira et al 2023). This indicated that soil condition plays a significant role at the lower level.…”
Section: Assessments Of the Component Effect And Importance Factors A...mentioning
confidence: 99%